Between Mom and Jo a novel - Peters, Julie Anne. (New York Little, Brown, 2006)
Fourteen-year-old Nick has a three-legged dog named Lucky 2, some pet fish, and two mothers, whose relationship complicates his entire life as they face prejudice, work problems, alcoholism, cancer, and finally separation.
"Megan Tingley Books"
First published in hardcover in 2006 by Little, Brown and Company
UCWS-2692g donated by Prof. Eric Julian Manalastas - January 2016
Keywords: Mothers and sons -- Fiction; Lesbians -- Fiction; Family problems -- Fiction; Prejudices -- Fiction